1995
DOI: 10.1080/00032719508000346
|View full text |Cite
|
Sign up to set email alerts
|

Precise Measurement of Chlorine Isotopes Based on Cs2Cl2by Thermal Ionization Mass Spectrometry

Abstract: An improved procedure for preciee meaeurement of chlorine isotope ratioe in geological eamplee baeed on CerC1+ ion by thermal ioniration maee epectrometry ie reported. Uaing thie procedure the a'Cl/aaCl ratio of N18T SRM 976 ie determined to be 0.318929f0.000028(1~) 1296 XIAO, ZHOU, AND LIU with a precieion of 0.009%(1a). The procedure hae been eucceeefully applied t o etudy t h e variation of chlorine ieotopic aompoeitione in seawater and t o determine atomic weight of chlorine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 5 publications
1
13
2
Order By: Relevance
“…The ion current intensity obtained in this study (2-3 × 10 -13 A, 2 µg-Cl loaded) was much lower than the intensity reported by Xiao et al (1995) (7 × 10 -12 A, 10 µg-Cl loaded), but higher than the value reported by Magenheim et al (1994) (4 × 10 -14 A, 2 µg-Cl loaded). The Cl isotopic ratio of seawater measured in this study was 0.319794 ± 0.000051 (average of run 1-25 ± 1σ SD ).…”
Section: Comparison Of Mass Spectrometric Methodscontrasting
confidence: 51%
See 3 more Smart Citations
“…The ion current intensity obtained in this study (2-3 × 10 -13 A, 2 µg-Cl loaded) was much lower than the intensity reported by Xiao et al (1995) (7 × 10 -12 A, 10 µg-Cl loaded), but higher than the value reported by Magenheim et al (1994) (4 × 10 -14 A, 2 µg-Cl loaded). The Cl isotopic ratio of seawater measured in this study was 0.319794 ± 0.000051 (average of run 1-25 ± 1σ SD ).…”
Section: Comparison Of Mass Spectrometric Methodscontrasting
confidence: 51%
“…Although Cl in seawater is isotopically homogeneous with variations less than the analytical precision, it is possible that the analytical methods could be improved to detect these variations (Xiao et al, 1995). In the case of mass spectrometry of CH 3 Cl, reference CH 3 Cl gas is introduced into the spectrometer, and ion beams are measured alternately in the sample and the reference for precise relative measurement (Long et al, 1993;Musashi et al, 1998).…”
Section: Cscl Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CsCl solution was then used for the mass spectrometry analysis. The mass spectrometry analysis is basically the same as that reported by Xiao and Zhang (1992); Xiao et al (1995) and Vengosh et al (1989): A VG 354 thermal ionization mass spectrometer was used for chlorine isotope measurements. The single tantalum filament heated at a current of 3.0 A for 1 h in a vacuum system, was first treated with a graphite slurry of 3 µL to coat the center of the filament.…”
Section: Sample Collection and Measurementsmentioning
confidence: 96%